Varying amounts of alfalfa meal in the rations of spring pigs and in dry lot. - Aubel, C.E. (Kansas Agricultural Experiment Station, 2011)
Summer of 1954 test with spring pigs was to get information on the maximum use of alfalfa meal in protein supplemental mixtures for pigs in the dry lot. Four lots of pigs were self-fed shelled corn and a mixed protein supplement. Lot 1 pigs were fed sudangrass pasture and self-fed a protein supplement of 4 parts tankage, 4 parts soybean meal, 1 part cottonseed meal, and 1 part alfalfa meal. Lot 2 received the same protein supplement as Lot 1 for 38 days or until the pigs weighed 100 pounds. They were then removed from the pasture and put into a dry lot and fed a protein supplement of equal parts tankage and alfalfa meal until the close of the experiment, when they weighed 197 pounds. Lot 3 was fed in the dry lot the entire feeding period on a protein mixture of 4 parts tankage, 4 parts soybean meal, and 3 parts alfalfa meal. Lot 4 was fed in the dry lot the entire feeding period with an increased alfalfa meal allowance, a protein supplement mixture of 5 parts tankage, and 5 parts alfalfa meal.
Keywords: Swine; Alfalfa meal; Protein; Gain